2018
DOI: 10.1097/md.0000000000011591
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value and susceptibility of BAX rs4645878 polymorphism in cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The gene encoding Bax protein is located on chromosome 19q13.3 and is controlled by p53. [32][33][34] The results of our study showed that the expression of the Bax gene significantly increased in A-172 cells (P < 0.01), but no significant change was observed in U251 cells. That may be due to a mutation of the p53 gene in U251 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding Bax protein is located on chromosome 19q13.3 and is controlled by p53. [32][33][34] The results of our study showed that the expression of the Bax gene significantly increased in A-172 cells (P < 0.01), but no significant change was observed in U251 cells. That may be due to a mutation of the p53 gene in U251 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating these SNPs in pregnancy disorders are scarce. However, the BAX-248G/A SNP has attracted much attention to malignant disorders [36,40]. In this context, low levels of BAX expression in untreated CLL patients are associated with BAX-248GA/AA genotype carriers [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is suggested that BAX-248G/A has no influence on cancer susceptibility [35,36]. The effect of SNP BAX-248G/A on the expression levels of the protein in CLL patients is still controversial [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis suggested that BAX gene polymorphisms were significantly associated with unfavorable prognosis in cancers. 27 As for CDKN1A, the mRNA and protein expression levels of CDKN1A were significantly up-regulated in many cancer tissues. The high expression of CDKN1A is associated with progression and poor prognosis of many tumors like breast cancer and gastric cancer.…”
Section: Discussionmentioning
confidence: 96%
“…BAX (BCL‐2 Associated X) is an important modulator of apoptosis. A systematic review and meta‐analysis suggested that BAX gene polymorphisms were significantly associated with unfavorable prognosis in cancers . As for CDKN1A, the mRNA and protein expression levels of CDKN1A were significantly up‐regulated in many cancer tissues.…”
Section: Discussionmentioning
confidence: 99%